EFFECT OF GARLIC (Allium sativum) SUPPLEMENTATION ON GROWTH PERFORMANCE AND CARCASS CHARACTERISTICS OF BROILER CHICKENS (FUDMA Journal of Agriculture and Agricultural Technology, 2022)
The study was conducted to investigate the effect of garlic supplementation on the growth performance and carcass characteristics of broiler chickens. One hundred and twenty (120) day old chicks of mixed sexes were randomly allotted into four treatment groups, thirty birds per treatment and were replicated three times with ten birds per replicate in a complete randomized design. Four test diets were formulated and designated as T1 for control, while T 2,  3, and 4 with  inclusion levels  of garlic powder at 0g/kg, 20g/kg, 15g/kg and 10g/kg respectively.  The study lasted for eight weeks.   The parameters investigated were growth performance (initial weight, final weight, weekly body weight gain,  percent dressed weight, feed intake (kg), feed conversion ratio, and mortality) and carcass characteristics. Cut-up parts of broiler chickens (head, neck, wings, drumsticks, thigh chest, back, shank) and visceral organs ( heart liver, kidney, spleen , pancreas, gizzard, abdominal fat, proventriculus and intestine). Data generated were subjected to analysis of variance and significant differences were separated using Least Significant Difference. The results of growth performance showed  that there were no significant (P>0.05) differences  in the parameters measured, except percentage dressed weight that showed significant difference with T1 having a higher value of (64.33%) which was closely followed by T4 with 62.60 %,  T2 with 61.10 % and the least  value was T3  with 54.53 %. The result of the study showed that garlic powder had no significant effect on body weight gain, carcass characteristics and feed conversion ratio.
Keywords: Supplements; chickens; Carcass characteristics; garlic